2017
DOI: 10.1155/2017/9092120
|View full text |Cite
|
Sign up to set email alerts
|

2D-Shear Wave Elastography in the Evaluation of Parathyroid Lesions in Patients with Hyperparathyroidism

Abstract: Background and Aims 2D-shear wave elastography (2D-SWE) is a relatively new elastographic technique. The aim of the present study is to determine the values of the elasticity indexes (EI) measured by 2D-SWE in parathyroid benign lesions (adenomas or hyperplasia) and to establish if this investigation is helpful for the preoperative identification of the parathyroid adenoma. Material and Methods The study groups were represented by 22 patients with primary or tertiary hyperparathyroidism, diagnosed by specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…Also, the region-of-interest field dimensions are not fixed as in most of the ARFI devices (0.5 × 0.6 cm) and can be changed accordingly to the size of the analyzed lesion. The only study performed with the use of the same method and device (Supersonic Imagine Aixplorer system), on significantly smaller group of patients ( n = 22), revealed similar results to our study–significantly higher parathyroid elasticity than surrounding thyroid tissue [ 28 ], but the authors did not include thyroid lesions in the assessment.…”
Section: Discussionsupporting
confidence: 83%
“…Also, the region-of-interest field dimensions are not fixed as in most of the ARFI devices (0.5 × 0.6 cm) and can be changed accordingly to the size of the analyzed lesion. The only study performed with the use of the same method and device (Supersonic Imagine Aixplorer system), on significantly smaller group of patients ( n = 22), revealed similar results to our study–significantly higher parathyroid elasticity than surrounding thyroid tissue [ 28 ], but the authors did not include thyroid lesions in the assessment.…”
Section: Discussionsupporting
confidence: 83%
“…Application of SWE with Virtual Touch tissue imaging quantification (VTIQ) enabled the differentiation between parathyroid adenoma and hyperplasia, as well as cervical lymph nodes [124]. Golu et al suggested that the cutoff value for SWE-Mean should be set at 12.5 kPa to provide an accurate diagnosis of parathyroid adenoma [70]. According to researchers, subjects with SWE-Mean value lower than 12.5 kPa present a high probability of parathyroid adenoma presence.…”
Section: Shear Wave Elastographymentioning
confidence: 99%
“…Parathyroid lesions also need to be differentiated from other neck lesions, such as thyroid nodules and lymph nodes (14). After evaluating 2D shear wave USE features of pathologically confirmed PAs, Golu et al .…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound elastography (USE) is a non-invasive and dynamic technique that objectively evaluates tissue hardness by measuring tissue elasticity (14, 15, 16). The principle for USE is based on the higher likelihood of softer tissues to deform under compression by an external force compared with harder tissues (17).…”
Section: Introductionmentioning
confidence: 99%